Neoadjuvant Therapy Combined With Oncoplastic Reduction for High-Stage Breast Cancer Patients. (June 2017) - Broecker, Justine S.; Hart, Alexandra M.; Styblo, Toncred M.; Losken, Albert
Abstract : Objective: Oncoplastic surgery has been shown to be a good alternative to breast conservation surgery (BCS) alone for patients with breast cancer. Its role in patients with advanced disease is unclear. In this study, we evaluate the safety of oncoplastic BCS (OBCS) in patients who received neoadjuvant therapy (NT) for high stage breast cancer. Methods: The oncologic outcomes of consecutive patients classified as high stage (>T2 or at least N1) who received NT followed by BCS at EUH by a single breast surgeon (T.M.S.) from September 2004 until June 2015 were compared with those who received BCS combined with an oncoplastic reduction. Patients were surveyed using the BREAST-Q to determine their satisfaction after surgery. Results: A total of 87 patients were included in this series. The mean initial tumor size (4.37 vs 2.56 cm), the weight of the surgical specimen, and the post-NT tumor size were all larger in the OBCS group as compared with BCS alone (1.54 vs 1.29 cm). The mean follow-up was 44 months. The average percent reduction in tumor size in response to NT was slightly greater in the OBCS group (61 vs 52%). Oncologic outcomes were similar for OBCS reduction and BCS groups, respectively: positive margin rate, reexcision rate, completion mastectomy rate, local recurrence rate, and 5-year DSS. Patient satisfaction was similar between the 2 groups. Conclusions: The oncoplastic approach in high stage patients treated with neoadjuvant systemic Powered by Editorial Manager and ProduXion Manager from Aries Systems Corporation therapy appears to be as safe and effective when compared to BCS alone. Oncoplastic BCS paired with NT broadens the indication for BCS for patients with larger tumor size.